Eradication of Enterococcus faecalis Biofilms on Human Dentin - Rosen, Eyal; Tsesis, Igor; Elbahary, Shlomo; Storzi, Nimrod; Kolodkin-Gal, Ilana (Frontiers in Microbiology, 2016)
Objectives: This work assesses different methods to interfere with Enterococcus faecalis biofilms formed on human dentin slabs. Methods: First, methods are presented that select for small molecule inhibitors of biofilm targets using multi-well polystyrene biofilm plates. Next, we establish methodologies to study and interfere with biofilm formation on a medically relevant model, whereby biofilms are grown on human root dentin slabs. Results: Non-conventional D-amino acid (D-Leucine) can efficiently disperse biofilms formed on dentin slabs without disturbing planktonic growth. Cation chelators interfere with biofilm formation on dentin slabs and polystyrene surfaces, and modestly impact planktonic growth. Strikingly, sodium-hypochlorite, the treatment conventionally used to decontaminate infected root canal systems, was extremely toxic to planktonic bacteria, but did not eradicate biofilm cells. Instead, it induced a viable but non culturable state in biofilm cells when grown on dentin slabs. Conclusions: Sodium-hypochlorite may contribute to bacterial persistence. A combination of the methods described here can greatly contribute to the development of biofilm inhibitors and therapies to treat Enterococcus faecalis infections formed in the root canal system.